2010
DOI: 10.3109/00016350903431118
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders and oral health-related quality of life. A systematic review

Abstract: The reviewed studies convincingly demonstrated that OHRQoL was negatively affected among TMD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
215
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(249 citation statements)
references
References 40 publications
20
215
0
14
Order By: Relevance
“…There is increasing interest in oral health-related quality of life (OHRQoL) (15), a multifactorial construct that assesses the adverse effects of orofacial disease on normal oral-related functions (16). A systematic review in 2010 (15) reported that the most widely used OHRQoL instrument was the Oral Health Impact Profile (OHIP), which has been translated and validated in several languages, including Chinese, German, and Swedish (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing interest in oral health-related quality of life (OHRQoL) (15), a multifactorial construct that assesses the adverse effects of orofacial disease on normal oral-related functions (16). A systematic review in 2010 (15) reported that the most widely used OHRQoL instrument was the Oral Health Impact Profile (OHIP), which has been translated and validated in several languages, including Chinese, German, and Swedish (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Oral diseases such as caries and periodontitis can affect various aspects of life and quality of life (21). Several studies reported that the adverse effects on OHRQoL are worse for TMDs (15,22) than for periodontal, dental (23), and neurological/ vascular orofacial pain conditions (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their systemat- ic review, some, but not all, reports suggested that TMDs have a greater impact on OHQoL than other orofacial diseases/illnesses or conditions. 21 …”
Section: Discussionmentioning
confidence: 99%
“…A somatória ou a exacerbação desses sintomas acaba por limitar ou mesmo incapacitar o indivíduo em suas atividades diárias, causando redução significativa em sua qualidade de vida (Bagis et al, 2012;Dahlström, Carlsson, 2010;Kostrzewa-Janicka et al, 2013). O diagnóstico é feito por meio de exame físico, com avaliação geral da cabeça e pescoço, palpação dos músculos mastigatórios, análise oclusal, exame da abertura e fechamento da mandíbula e palpação da ATM.…”
Section: Disfunções Temporomandibularesunclassified